2023
DOI: 10.1002/lary.30642
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Disease in Adults with Cystic Fibrosis in the Era of CFTR Modulators

Abstract: ObjectivesChronic rhinosinusitis (CRS) is prevalent in people with cystic fibrosis (PwCF) and is often refractory to treatments. Uncontrolled CRS might negatively impact the lower airways and the quality of life. The aim of this study is to evaluate the burden of cystic fibrosis (CF)‐related CRS in the era of CF transmembrane conductance regulator (CFTR) modulators.MethodsAdult PwCF were asked to fill in a questionnaire on sinonasal complaints, they underwent a nasal endoscopy, bacteriological sampling, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This study does not reflect on the evolving field of novel medical agents such as CFTR modulator therapies and its impact on future management of sinus disease in CF patients and improved allograft outcomes. As clinicians experience on a daily basis, the modulator therapies provide a promising conservative treatment option with great impact on symptoms and clinical signs (e.g., polyps) and are already changing current treatment protocols [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study does not reflect on the evolving field of novel medical agents such as CFTR modulator therapies and its impact on future management of sinus disease in CF patients and improved allograft outcomes. As clinicians experience on a daily basis, the modulator therapies provide a promising conservative treatment option with great impact on symptoms and clinical signs (e.g., polyps) and are already changing current treatment protocols [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…and was designed to accommodate paired data analysis with a two-sided test, an alpha (significance) level of 0.05, and a desired statistical power of 90%. The Modified Lund-Mackay score was used as outcome parameter to build the power calculation, as previous literature has shown that patientreported outcome measures poorly correlate with objective disease extent (22) .…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Prior to this study, no (pilot)data were available for the TEZ/IVA subgroup. Consequently, the power analysis was conducted using the baseline Modified Lund-Mackay scores from our preexisting patient registry, which consisted of 122 patients with a mean score of 11.69 and a standard deviation of 6.31 (22) . To detect a MCID of >5, power analysis revealed an estimated sample size requirement of 19 participants for this specific subgroup.…”
Section: Sample Size Calculationmentioning
confidence: 99%